(untitled) (Journal of Economic Research & Business Administration, 2017)
The productive application of project management in the commercial sector gave impetus to the use of project management tools and performance of public authorities. The article is devoted to the description of the process of implementing project management in the system of public administration of the Republic of Kazakhstan. Experience in the use of project management in governmental bodies of the country has been studied. At the same time, the process of implementing project management in the authorities of the Russian Federation was analyzed to explore the experience of the near abroad. The experience of using the project management of Kazakhstan and the Russian Federation in carrying out large national projects such as EXPO-2017 and SOCHI-2014 has been studied.